(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Gudovsek O. A. Features of the content of education in primary schools in Japan. In the article analyzes the features of training in modern elementary school Japan. Based on content analysis of primary education highlighted its most important components, is disclosed specifics school subjects. It was determined that an important place in the educational content of Japanese elementary school occupies moral education, as well as extra-curricular education work, the participation of children in national holidays.